Digital filmmaking for kids for dummies - Willoughby, Nick (--For dummies., 2015)
Digital Filmmaking For Kids makes it easy to get up and running with digital filmmaking! This fun and friendly guide walks you through a ton of cool projects that introduce you to all stages of filmmaking. Packed with full-color photos, easy-to-follow instruction, and simple examples.